2021
DOI: 10.3390/agriculture11121298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Autumn Incorporation of Rice Straw and Application of Lime Nitrogen on Methane and Nitrous Oxide Emissions and Rice Growth of a High-Yielding Paddy Field in a Cool-Temperate Region in Japan

Abstract: The effects of autumn plowing and lime nitrogen application on rice straw decomposition, CH4 and N2O emission and rice growth in the following year in a high-yielding rice cultivated paddy field were evaluated for two years. The experimental plots were set up, combining different times of rice straw (750 g m−2) incorporation into the soil by plowing (autumn or the following spring), with and without lime nitrogen application in autumn (5 g-N m−2). Autumn plowing promoted the decomposition of rice straw, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, straw anaerobic decomposition in the deep soil layer before rice transplanting produces reducing substances that inhibit crop root growth (Huang, Ma, et al, 2020; Huang, Pan, et al, 2020). Takakai et al (2021) reported that returning straw to the soil after the rice was harvested in autumn promoted the decomposition of the straw and improved the growth and yield of the second‐year rice. Occasional use of segmented PT (winter plowing + rotary tilling before rice transplanting) has the potential to increase rice yields and maintain soil health in ratoon rice systems (Wang, He, et al, 2020; Wang, Qi, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, straw anaerobic decomposition in the deep soil layer before rice transplanting produces reducing substances that inhibit crop root growth (Huang, Ma, et al, 2020; Huang, Pan, et al, 2020). Takakai et al (2021) reported that returning straw to the soil after the rice was harvested in autumn promoted the decomposition of the straw and improved the growth and yield of the second‐year rice. Occasional use of segmented PT (winter plowing + rotary tilling before rice transplanting) has the potential to increase rice yields and maintain soil health in ratoon rice systems (Wang, He, et al, 2020; Wang, Qi, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, LMC may not inhibit N 2 fixation because of its slow decomposition (mineralization). The lower amount and percentages of N accumulation derived from N 2 fixation than the values shown in Section 2 (Figure 4, [19]) may be due to the fact that the study site was located in a reclaimed land and soil N fertility was high [46]. Therefore, soil N uptake via soybean roots could be high and dependence on symbiotic N 2 fixation could be low.…”
Section: Cultivation Managements For the Mitigation Of N Loss From Pa...mentioning
confidence: 76%